O florescimento da consciência moral e a lei natural em Jacques Maritain - Ratti, Renato (2019)
The French philosopher of the twentieth century, Jacques Maritain, then Ambassador of the Holy See at UNESCO, supported by the studies of Summa Theologicae by Thomas Aquinas, effectively contributed to the preparation of the Universal Declaration of Human Rights, published in 1948, philosophical view of that conquest is the Natural Law. Especially in the work "Man and the State," Maritain elaborates the "Confessions" of the Declaration and reveals that the idea of progress in historical terms of humanity is associated with the rise of moral consciousness and the understanding of the natural law considered the essential practical reason to obtain a consensus. This is to say in proportional terms that the greater the understanding of man on the so-called "Natural Law," the greater will be the moral elevation of self and the enhancement of societies, including the Institutions. The present research consists in understanding this mentioned "becoming" or progress of the moral conscience of the man and his relationship with the natural law. It can be affirmed, in a certain sense, that man develops morally and spiritually the more he understands this Law. The 1948 Declaration stands as a great achievement of humanity in the field of Human Rights, its retrocession not possible, however , have been edited as a Treaty of Peace and endure as glittering moral treasure of contemporaneity